THE NATIONAL IDEOLOGY OF INDEPENDENT UZBEKISTAN: FOUNDATIONS AND SIGNIFICANCE (American Journal of Interdisciplinary Research and Development, 2025)
This article examines the key aspects of the ideology of independent Uzbekistan and its main principles and objectives. Special attention is paid to the factors influencing the formation of this ideology and its significance for the spiritual, socio-economic, and political development of the country. The mechanisms of educating the younger generation in the spirit of patriotism and national self-awareness are analyzed, as well as the influence of ideology on Uzbekistan's foreign policy and international cooperation.